Peningkatan Sumber Daya Manusia melalui Pendidikan Islam - Nurdin Nurdin (Dinamika Ilmu, 2011)
Education is the interaction between humans and the environment including the natural environment and environmental human being. The interaction is not simply the result of human interaction with nature and with fellow human beings, but rather the result of human potential in an optimal developmet accordance with an open space for the development of innovation and creativity. Islamic education is expected to be further developed so that the Islamic educational institutions have appeal, because it is more outgoing and global dimension. Developmenting quality of human resources require different prerequisites in its implementation, including human life environment should provide opportunities for the development of learners to develop in accordance with the potential available to it. Islamic education in spiritual growth and moral individuals will be able to help strengthen the faith, belief, and recognition of God Almighty, through the legal, moral and religious teachings, thereby guiding learners in implementing faith in God Almighty and a deep understanding of religious teachings and value in life in her behavior, and relationship with Allah SWT with fellow human beings and all creatures, will reinforce the importance of moral education and spirituality in facing globalization.